Enhanced electrochemical and mechanical performance of BN reinforced Ni-P based nanocomposite coatings - Izza Fatima (17346967) (2022)
Adequate corrosion protection and improved mechanical properties are necessary requirements to overcome operational costs in the industries. Ni-P based coatings are known to possess better superior corrosion resistance than its counterparts. Boron Nitride nanoparticles (BNNPs) are well known refractory material with higher hardness and chemically inert nature suitable for reinforcement. In the current investigation, the effect of incorporation and increasing concentration of BNNPs in Ni-P matrix in thoroughly investigated in terms of mechanical and electrochemical performances. Successful incorporation of BNNPs within the Ni-P matrix was achieved by employing tailored Watts bath and optimized deposition parameters. The addition and increment of BNNPs reveal a significant impact on the characteristics of pure Ni-P coatings. Improvement in the structural, morphological, mechanical and corrosion behavior of BNNPs reinforced nanocomposite coatings can be ascribed to uniform incorporation of BNNPs in the deposit leading to the dispersion hardening effect that enhances strength to the coating improving surface hardness up to 58 % in comparison to pure Ni-P coating. Moreover, reduction in the active area caused by inert BNNPs leads to the improvement in corrosion resistance properties with protection efficiency (PE%) reaching up to 95 % for Ni-P-1.5 g/L BN nanocomposite coating in comparison to the bare mild steel substrate. BNNPs reinforced Ni-P based nanocomposite coatings provide a possible choice for their application in many industries like in the aerospace, automotive, marine, oil and gas industry. Other Information Published in: Diamond and Related Materials License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.diamond.2022.109454